Activity Descriptors as Tools for Designing Highly Efficient Electrocatalysts for Water Splitting - Gomaa, Aya (AUC Knowledge Fountain, 2024)
There is an uprising urge to design efficient, active, and durable catalysts to achieve sustainable hydrogen production. The unambiguity of which material should be used pushed the scientific community to devote enormous efforts in exploring different elements with different ratios on trial and error bases. However, the bridge between the theoretical calculation and the experiments introduced a new realm of designing efficient catalysts by introducing the concept of activity descriptors. In the first part of the thesis, the ability to convert waste stainless steel (SS) 316L meshes into highly eﬃcient and durable oxygen evolution reaction (OER) catalysts is demonstrated. The activity of the resulted electrocatalysts is in the order anodized SS annealed in oxygen (ASS-O2) > anodized SS annealed in hydrogen (ASS-H2) > anodized SS annealed in air (ASS-Air). The ASS-O2 showed an impressive low overpotential (η) of 280 mV at 10 mA/cm2, which is 120 mV less than that of the as-received SS (SS-AR), with a low Tafel slope of 63 mV dec−1 in 1 M KOH. These ﬁndings have also been asserted by the estimated electrochemical active surface area, electrochemical impedance spectroscopy analysis, Mott−Schottky analysis, and the calculated turnover frequency, aﬃrming the superiority of the ASS-O2 electrocatalyst over the ASS- H2 and ASS-Air counterparts. The high activity of the ASS-O2 electrocatalyst can be ascribed to the surface composition that is rich in Fe3+ and Ni2+ as revealed by the X-ray photoelectron spectroscopy analysis. The simple method of anodization and thermal annealing in O2 at moderate conditions (450 °C for 1 h) lead to the formation of a SS mesh -based OER electrocatalyst with activity exceeding that of the state-of-the-art IrO2/RuO2 and other complex modiﬁed SS catalysts. These results were also conﬁrmed via density functional theory calculations, which unveiled the OER reaction mechanism and elucidated the d-band center as an activity descriptor in diﬀerent SS samples with diﬀerent oxygen content. The presence of oxygen moved the d-band center closer to the Fermi level in the case of ASS-O2, explaining its superior activity. While for the second part of the thesis, a one-step hydrothermal synthesis method is demonstrated for the fabrication of flower-shaped spinel CoFe2O4 nanosheets on Ni foam at various pHs with different cation distribution. The XPS and Raman analyses revealed the cation distribution of Co and Fe as the main factor determining the catalytic activity of the material, which has been confirmed both experimentally and computationally. The catalyst with the largest δ showed η as low as 66 mV at -10 mA cm-2 with exceptional stability for 44 hours of continuous electrolysis in 1 M KOH. Our study demonstrates cation distribution as a catalytic activity descriptor of spinels for HER.